1985
DOI: 10.1128/mcb.5.1.75
|View full text |Cite
|
Sign up to set email alerts
|

Specific Saccharomyces cerevisiae genes are expressed in response to DNA-damaging agents.

Abstract: When exposed to DNA-damaging agents, the yeast Saccharomyces cerevisiae induces the expression of at least six specific genes. We have previously identified one damage inducible (DIN) gene as a gene fusion (din-lacZ fusion) whose expression increases in response to DNA-damaging treatments. We describe here the identification of five additional DIN genes as din-lacZ fusions and the responses of all six DIN genes to DNA-damaging agents. Northern blot analyses of the transcripts of two of the DIN genes show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(67 citation statements)
references
References 53 publications
(40 reference statements)
2
65
0
Order By: Relevance
“…Because mRNA analysis for the RAD52 gene indicated that this gene is not induced in response to X-ray damage, we constructed a gene fusion with the 5' region of RAD52 to serve initially as a negative control for the induction of RAD54. It has already been observed that various DNAdamaging agents induce a specific set of mRNA transcripts (22) and cloned lacZ fusions (31). The fact that we see little or no induction of RAD52 constructs while we do see a clear induction of RAD54 confirms that DNA damage to cells induces a specific subset of genes and is not a general induction signal for all genes.…”
Section: Discussionsupporting
confidence: 76%
“…Because mRNA analysis for the RAD52 gene indicated that this gene is not induced in response to X-ray damage, we constructed a gene fusion with the 5' region of RAD52 to serve initially as a negative control for the induction of RAD54. It has already been observed that various DNAdamaging agents induce a specific set of mRNA transcripts (22) and cloned lacZ fusions (31). The fact that we see little or no induction of RAD52 constructs while we do see a clear induction of RAD54 confirms that DNA damage to cells induces a specific subset of genes and is not a general induction signal for all genes.…”
Section: Discussionsupporting
confidence: 76%
“…Yeast and bacteria were grown as described (6). 4NQO (Sigma) was prepared and stored as a stock solution at 0.5 mg/ml as described by Ruby and Szostak (17 (7,15,25). A second RAD2-lacZ fusion (pRF2002) utilized an EcoRV site in the RAD2 coding region and expressed more f3-galactosidase activity than did pRF2001.…”
Section: Methodsmentioning
confidence: 99%
“…A qualitative filter assay for 3-galactosidase (15) was used to screen for plasmids containing the E. coli lacZ gene in the correct transcriptional and translational alignments relative to the RAD genes. Quantitative assays for /3-galactosidase in liquid cultures of yeast were carried out with extracts prepared as described (17). Enzyme activity was measured by using O-nitrophenyl (3-Dgalactopyranoside or 4-methylumbelliferyl /3-D-galactoside as substrates.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[41][42][43][44][45] This became clear in the late 1990s with the use of high-throughput microarray technologies. 46 Genome-wide expression analysis in yeast has revealed that in response to replication stress induced by methyl methane sulphonate (MMS), ionizing radiation (IR), hydroxyurea (HU) and UV radiation, hundreds of genes are either induced or repressed.…”
Section: Checkpoint-dependent Transcriptional Regulation In Yeastmentioning
confidence: 99%